Watershed and river basin management - Zainudin, Zaki; Koning, Wendell; Weyand, Michael; Kelderman, Peter; Crabtree, Bob (International Water Association, 2012)
Leaps and bounds have been made in areas related to river basin management on a global scale, in line with vari- ous technological advances of the 21st century. We review six emerging trends related to water science, research and management.